Performance and Biochemical Responses in Early-Weaned Piglets Fed Diets with Different Protein and Zinc Levels - Mei, Yang; Zhi-Sheng, Wang; An-Guo, Zhou (Pakistan Journal of Nutrition, 2009)
A 2x2 factorial experiment was used to investigate the interaction between dietary Crude Protein (CP) concentration (23 and17%) and zinc supplementation (100 and 3,000 mg/kg, from zinc oxide) on performance and biochemical responses in 32 crossbred piglets weaned at 21 days of age (4 groups of 8 each, 6.3±0.4 kg live weight). Pigs were offered four diets for 28 days after weaning, i.e., 23% CP +100 mg/kg Zn; 17% CP + 100 mg/kg Zn; 23% CP + 3,000 mg/kg Zn and 17% CP + 3,000 mg/kg Zn. There were no interactions between CP and Zn concentration on performances except for on ADG during 3 and 4 weeks. As CP content increasing, ADG, ADFI and Gain: Feed ratio (G:F) were increased across feeding period (p